PENYULUHAN MENGENAI POLA HIDUP SEHAT UNTUK MENCEGAH PENYAKIT HIPERTENSI - Anastasya Shinta Yuliana; Bobi Handoko (LPPM Universitas Awal Bros, 2024)
High blood pressure, better known as hypertension, is a disease that has received attention from all levels of society, considering the impacts it has both short and long term, so it requires comprehensive and integrated long-term management. Hypertension causes high rates of morbidity (sickness) and mortality (death). Hypertension is a disease that arises due to the interaction of various risk factors that a person has. Various studies have linked various risk factors to the emergence of hypertension. Hypertension, currently there is a tendency that urban communities suffer from hypertension more than rural communities. This, among other things, is related to the lifestyle of city residents which is associated with the risk of hypertension, such as stress, obesity, lack of exercise, smoking, alcohol and eating foods that are high in fat. As age increases, almost everyone experiences an increase in blood pressure, systolic pressure continues to increase until the age of 80 years and diastolic pressure continues to increase until the age of 55-60 years, then decreases slowly or even decreases drastically.